A simple blood test expedites the diagnosis of glucose transporter type 1 deficiency syndrome. Issue 1 (July 2017) - Gras, Domitille; Cousin, Christelle; Kappeler, Caroline; Fung, Cheuk‐Wing; Auvin, Stéphane; Essid, Nouha; Chung, Brian Hy; Da Costa, Lydie; Hainque, Elodie; Luton, Marie‐Pierre; Petit, Vincent; Vuillaumier‐Barrot, Sandrine; et al.
Abstract : Glucose transporter type 1 (GLUT1) deficiency syndrome (GLUT1‐DS) leads to a wide range of neurological symptoms. Ketogenic diets are very efficient to control epilepsy and movement disorders. We tested a novel simple and rapid blood test in 30 patients with GLUT1‐DS with predominant movement disorders, 18 patients with movement disorders attributed to other genetic defects, and 346 healthy controls. We detected significantly reduced GLUT1 expression only on red blood cells from patients with GLUT1‐DS (23 patients; 78%), including patients with inconclusive genetic analysis. This test opens perspectives for the screening of GLUT1‐DS in children and adults with cognitive impairment, movement disorder, or epilepsy. Ann Neurol 2017;82:133–138